2019
DOI: 10.1111/gcb.14864
|View full text |Cite
|
Sign up to set email alerts
|

The Paris Agreement objectives will likely halt future declines of emperor penguins

Abstract: The Paris Agreement is a multinational initiative to combat climate change by keeping a global temperature increase in this century to 2°C above preindustrial levels while pursuing efforts to limit the increase to 1.5°C. Until recently, ensembles of coupled climate simulations producing temporal dynamics of climate en route to stable global mean temperature at 1.5 and 2°C above preindustrial levels were not available. Hence, the few studies that have assessed the ecological impact of the Paris Agreement used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 63 publications
1
66
0
Order By: Relevance
“…However, as these areas away from the coast are more northerly, they will be in warmer areas and therefore will be more likely to be susceptible to early sea ice loss (Ainley et al 2010). Jenouvrier et al (2019) identified colonies that are projected to be either quasi-extinct, endangered, vulnerable or stable by the end of this century assuming a businessas-usual GHG emissions scenario and a climate-dependent-meta-population model. The revised map of emperor penguin distribution (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as these areas away from the coast are more northerly, they will be in warmer areas and therefore will be more likely to be susceptible to early sea ice loss (Ainley et al 2010). Jenouvrier et al (2019) identified colonies that are projected to be either quasi-extinct, endangered, vulnerable or stable by the end of this century assuming a businessas-usual GHG emissions scenario and a climate-dependent-meta-population model. The revised map of emperor penguin distribution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2019). The 12 colonies are all in areas where colonies are expected to become extinct or quasi-extinct by the end of the century (Jenouvrier et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gamelon et al., 2017; Hansen et al., 2019; Nater et al., 2018). When demographic data are available, forecasts can, and should account for uncertainty about population structure, initial population size, and in a metapopulation context, dispersal among local populations (Iles & Jenouvrier, 2019; Jenouvrier et al., 2020). For other species, like the blue mussels Mytilus trossulus described in Jaatinen et al.…”
Section: Figurementioning
confidence: 99%
“…Reliable forecasts of wildlife populations rely on methods that can account for these varied sources of uncertainty (bottom right; with blue-and green-shaded areas representing the proportion of total uncertainty associated with population model-and climaterelated sources respectively). Failing to account for uncertainties in population forecasts can result in biased inferences and overly confident predictions about how populations are likely to respond to future changes in climate metapopulation context, dispersal among local populations (Iles & Jenouvrier, 2019;Jenouvrier et al, 2020). For other species, like the blue mussels Mytilus trossulus described in Jaatinen et al (2021), it is impossible to track individuals and estimate demographic rates.…”
mentioning
confidence: 99%
“…270 000 breeding pairs in known colonies around the continent 25 , the species is severely threatened by global warming and expanding fishing activities in the Southern Ocean 15,26 , facing the risk to be nearly extinct within this century 27 . The most effective actions to protect the Emperor penguin from anthropogenic impacts would be a reduction in greenhouse gas emissions 26,27 as well as the establishment of MPAs throughout its habitat range 26 . However, little is known about the early life at sea of emperor penguins, even though their survival is crucial for the viability of the global population 28 .…”
mentioning
confidence: 99%